2021
DOI: 10.3892/mmr.2021.12370
|View full text |Cite
|
Sign up to set email alerts
|

A microRNA‑17‑5p/homeobox B13 axis participates in the phenotypic modulation of vascular smooth muscle cells

Abstract: Vascular smooth muscle cells (VSMCs) serve a decisive role in intimal hyperplasia, a common pathophysiological process that leads to numerous vascular disorders. The present study aimed to investigate the unknown mechanisms underlying VSMC phenotypic modulation and identified a novel microRNA (miRNA/miR)-17-5p/homeobox B13 (HOXB13) axis involved in the phenotypic switching, proliferation and migration of VSMCs. VSMCs were isolated from the thoracic aorta of Sprague-Dawley rats, cell proliferation was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Within the literature, the influence of miR-17 on SMC phenotype is species and contextdependent. It is associated with a contractile phenotype in both murine and rodent SMCs treated with the pro-proliferative platelet-derived growth factor-BB (PDGF-BB; [19,24]) and in human aortic SMCs treated with thrombospondin [20]; however, it can also promote dedifferentiation to a synthetic phenotype in rodent SMCs treated with oxidized LDL [21] and in a human aortic vascular SMCs cell line in response to inflammatory stimuli [23]. Furthermore, miR-17 is upregulated in the plasma of atherosclerosis patients and can promote atherosclerosis in mice [22].…”
Section: Discussionmentioning
confidence: 99%
“…Within the literature, the influence of miR-17 on SMC phenotype is species and contextdependent. It is associated with a contractile phenotype in both murine and rodent SMCs treated with the pro-proliferative platelet-derived growth factor-BB (PDGF-BB; [19,24]) and in human aortic SMCs treated with thrombospondin [20]; however, it can also promote dedifferentiation to a synthetic phenotype in rodent SMCs treated with oxidized LDL [21] and in a human aortic vascular SMCs cell line in response to inflammatory stimuli [23]. Furthermore, miR-17 is upregulated in the plasma of atherosclerosis patients and can promote atherosclerosis in mice [22].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, it maintains a contractile form of VSMCs by activation of PPARγ ( 12 ). In addition, Yu et al ( 67 ) demonstrated that HOXB13 is involved in the phenotypic modulation of VSMCs induced by platelet-derived growth factor-BB in the miR-17-5p-HOXB13 axis. Although the aforementioned findings have shown that the HOX gene is linked to vascular remodeling, key mechanistic insight into governing vascular remodeling remains poor and a gamut of HOX gene investigation, particularly in vivo exploration, is currently lacking, limiting our understanding of its causal role in vascular remodeling; thus, abundant work remains to be done in the future.…”
Section: A Central Role For Hox Genes In Atherosclerosismentioning
confidence: 99%
“…For example, mi-99a-5p alleviates atherosclerosis via regulating HOXA1 ( 30 ). In addition, the miR-17-5p/HOXB13 axis participates in the phenotypic modulation of VSMCs ( 67 ). In short, ncRNAs may regulate the expression of HOX genes and have a potential role in atherosclerosis.…”
Section: New Emerging Themes In Hox Gene Regulatory Circuitsmentioning
confidence: 99%
See 1 more Smart Citation